2011
DOI: 10.1111/j.1530-0277.2011.01588.x
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Clusterin Is Associated with Neuronal Apoptosis in the Developing Rat Brain upon Ethanol Exposure

Abstract: This study shows that nClu plays a pro-apoptotic role in ethanol-induced cell death in the developing brain, providing new insights for development of FASD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 47 publications
2
21
0
Order By: Relevance
“…To the best of our knowledge, they have distinct biological functions, e.g. sCLU reportedly can prevent cell death while nuclear can promote cell death (Kim et al 2012;Koltai 2014). To clarify the function of sCLU, we utilized intraventricular infusion of exogenous human ApoJ protein following CCI in mice.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, they have distinct biological functions, e.g. sCLU reportedly can prevent cell death while nuclear can promote cell death (Kim et al 2012;Koltai 2014). To clarify the function of sCLU, we utilized intraventricular infusion of exogenous human ApoJ protein following CCI in mice.…”
Section: Discussionmentioning
confidence: 99%
“…We previously proposed that nCLU sequesters the anti-apoptotic Bcl-1 family member, Bcl-xL, via its putative BH3 motif and releases bound Bax, thereby promoting apoptosis accompanied by activation of caspase-3 and release of cytochrome c (Kim and Choi, 2011; Kim et al, 2011; 2012; Lee et al, 2011). These results suggest a novel, nCLU-mediated apoptosis mechanism in normal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies have shown that the mode of death in these neurons is apoptosis [15]. We examined Apo J protein expression in the pons and hippocampus of early liveborn neonatal deaths comparing 12 cases with PSN to 15 controls lacking PSN on histology.…”
Section: Introductionmentioning
confidence: 99%